Evaluation of the activity and efficacy of Rosa canina vegetable oil as a depigmenting agent: a review study (Research, Society and Development, 2022)
The use of Rosa Mosqueta (Rosa rubiginosa) vegetable oil has been incessantly divulged in all kinds of social media with the promise of lightening skin spots. The present article aimed to study and demystify its effectiveness in skin hyperpigmentation processes, presenting as scientific methodology a literature review study of currrently existing literature on the subject.  The anti-melanogenic capacity of vegetable oil is associated with the inhibition of tyrosinase enzyme activity, promoted by a set of assets in its formula, such as linoleic, α-linolenic, lauric, stearic, oleic, myristic, behenic, palmitic, ascorbic, trans-retinoic, α-tocopherol, and quercetin acids. By analyzing the data in the literature there is evidence that in fact they play a role both in promoting emollient and healing actions, as in skin whitening, so its use becomes advantageous in the treatment of mild hyperpigmentation of the skin. The rosehip vegetable oil is a promising active in the field of cosmetology, but it still needs further studies, because it can promote major innovations in the cosmetics industry.